Tectonic evolution of the Triassic Songpan‐Ganzi basin as constrained by a synthesis of multi‐proxy provenance data. (8th September 2022) - Tang, Yan; Yin, An; Xu, Xi; An, Kaixuan; Zhang, Yunpeng
Abstract: The triangular Songpan‐Ganzi flysch terrane exposes a Triassic turbidite sequence with an average thickness of ca. 8 km. The sediments may have been accumulated in a remnant Paleo‐Tethyan ocean bounded by the converging North China, South China, and the Qiangtang terrane from three sides, or a back‐arc basin with an oceanic basement created during the Triassic closure of the Paleo‐Tethyan ocean. To differentiate the two competing models, we systematically reviewed the available provenance data that include U–Pb detrital zircon ages at the basin scale, paleocurrent directions, sandstone petrography, and heavy‐mineral assemblages from the Triassic Songpan‐Ganzi basin samples. We use the Kolmogorov–Smirnov tests to differentiate competing hypotheses for detrital‐zircon provenance interpretations and DZmix modelling to quantify relative contributions of detrital zircon from all potential source areas for the Triassic Songpan‐Ganzi deposits. The most important result of this work is that the Songpan‐Ganzi basin had a stable and locally derived source system: the western, central and eastern sub‐basins were mainly sourced from the north whereas the easternmost and southeastern sub‐basins were mainly sourced from westernmost South China (i.e., the Longmen Shan area) and the Qiangtang terrane. The stability of the source areas around the Songpan‐Ganzi basin throughout the Triassic is most compatible with the remnant ocean model that predicts a long‐lived marine basin with a pre‐Triassic oceanic/continental basement trapped between converging continental blocks during the Triassic. Abstract : DZmix modelling of the Songpan‐Ganzi detrital‐zircon age data supports the remnant ocean model.